If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 187 = -1u + 25 Reorder the terms: 187 = 25 + -1u Solving 187 = 25 + -1u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add 'u' to each side of the equation. 187 + u = 25 + -1u + u Combine like terms: -1u + u = 0 187 + u = 25 + 0 187 + u = 25 Add '-187' to each side of the equation. 187 + -187 + u = 25 + -187 Combine like terms: 187 + -187 = 0 0 + u = 25 + -187 u = 25 + -187 Combine like terms: 25 + -187 = -162 u = -162 Simplifying u = -162
| 6(2x)+2=84 | | 152-x=236 | | 25x^8-116x^4+64=0 | | 8x^2+20xy-12y^2= | | 8x+13y=102 | | (4x-pi)= | | 5x+4-x=20 | | -y+294=135 | | -18n+12=-16n-6 | | 25x^8-116x^4+16=0 | | -25+-15= | | 15x+4-x=20 | | (6+x)=(x-3) | | -36=-4(u+8) | | 3m^2+5=20 | | -22=4w-2 | | 2x^4+17x^2+8=0 | | .2y+1=6 | | x+35-3x=5 | | 2025t+5=13.5t+14 | | x-15=3x+3 | | -5m-11-2m+4=14 | | 4x^8-65x^4+16=0 | | 2y+7=y-7 | | (8-2x)3=12 | | 12 = q4+ 10 | | 18=3b+9 | | 2+3z=5 | | 4+3(x-7)=-7 | | 6(w-3)=24 | | 4x-18=x+6 | | 5m+5=2m-4 |